Should I Win or Should I not Lose? : A Research Framework Exploring the Role of Motivation in Processing Brand Related Information in Advergames - Ghosh, Tathagata; Rao, Venu Gopal (Indian Journal of Marketing, 2015)
Extant research dealing with information processing in advergames focuses mostly on players’ limited capacity aspect of attention and persuasion knowledge, persuasive potency of advergames, information-processing fluency, and the development of flow and arousal among players. One primary facet of advergames that remains under-investigated is the effect of game outcomes, that is, wins and losses, on players’ motivation and the influence of outcome-induced motivation on information processing. Furthermore, earlier studies predominantly considered players’ explicit memory like brand recall and recognition while ignoring a salient unconscious measure, namely implicit memory. This paper provides a conceptual framework that explored the influence of advergame outcomes and messages on players’ motivation and its subsequent impact on processing embedded brand elements. Conceptual fabric of the proposed model was derived from a motivational principle, regulatory focus theory, and implicit memory literature to explain how outcome-induced motivation influences players’ nature of information processing, implicit memory, emotions, and brand and game attitudes. Academic and managerial implications were also discussed.